THE FORMATION AND DEVELOPMENT OF NEW ERA EXPERIMENTAL THEATERS (International journal of artificial intelligence, 2026)
This article explores the experimental processes of 20 th and 21st-century theatrical art and the methodology behind the formation of new directions. Based on source materials, it analyzes the creative laboratories of great reformers such as K.S. Stanislavski, V.E. Meyerhold, B. Brecht, and J. Grotowski, as well as the concepts of "conditional theater," "biomechanics," and "poor theater." Furthermore, the role of experimental research in contemporary Uzbek theater and the issues of artistic integrity are highlighted.